Employee Loyalty as Seen in The English of Compensation, Organizational Culture, Work Motivation and Village Office Work Environment - Agus Suwoko; Sudarwati Sudarwati; Istiatin Istiatin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to determine and explain the influence of compensation, organizational culture, work motivation, and the work environment on the performance of village officials in Kasreman District, Ngawi. The population of this study was 50 village officials in Kasreman District, Ngawi, and a sample of 50 people using total sampling technique. Data collection used a questionnaire. Data analysis used Multiple Linear Analysis. The results showed that compensation, organizational culture, work motivation, and the work environment contributed 72.1% to performance, while the remaining 27.9% was explained by other variables not included in this study. This research suggests that village officials in Kasreman District, Ngawi, can improve their organizational culture and competency, and that leaders can manage employee workloads to enhance work experience and achieve maximum performance results.